Assessing the severity grading of acute cholecystitis according to Tokyo guidelines 2013 and outcome of conservative management - Iqbal, Asif; Hussain Shah, Fozia; Gani, Mubashir; Naqash, Sameer H.; Shah, Mubashir A. (International Journal of Research in Medical Sciences, 2025)
Background: Acute cholecystitis is most often triggered by gall stones. Gall stones are one of the most common disorders of the gastrointestinal tract, affecting about 10% of people in Western society. Methods: This prospective observational was conducted in the department of General Surgery, Sher e Kashmir Institute of Medical Sciences and SKIMS Medical College from September 2018 to August 2020 comprising of 112 patients. The severity of cholecystitis according to TG13 was noted. All the patients were managed conservatively. Patients were closely monitored for any change in severity. Results: A total of 112 patients were studied with male: female ratio of 1:3.5. The maximum number of patients were in the age group of 45 to 59 years with a mean age of 50.3 years, 63.4% of patients were associated with comorbidities. LFT was deranged in only 21.4% of the patients All the patients were assessed for the severity of illness according to the Tokyo guidelines (TG 13). 64 (57.1%) patients had mild illness, 43 patients (38.4%) had moderate illness and 05 patients (4.5%) had severe illness. 84.8% (95) of the patients improved by conservative management. 03 patients belonging to severe grade needed open surgical intervention. 01-patient died in postoperative period. Most of the patients had a hospital stay of less than 01 week with mean duration of 3.8 days. Most patients with mild to moderate disease were below 60 years. All the grades of severity were more common in females. Conclusions: Most patients with acute cholecystitis can be managed conservatively.